2022
DOI: 10.1002/acr.24867
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Response to Advanced Therapies in Rheumatoid Arthritis

Abstract: Objective We performed a study of tumor necrosis factor inhibitors (TNFi) compared to non‐TNFi biologic therapies in rheumatoid arthritis to test whether body mass index (BMI) modified the effect of each therapy. Methods We utilized data from CorEvitas. We studied 3 clinical outcomes based on the Clinical Disease Activity Index (CDAI) at 6 months from therapy initiation: 1) achievement of low disease activity (LDA); 2) a change as large as the minimum clinically important difference (MCID); and 3) the absolute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…To the best of our knowledge, there have been no prior studies investigating the influence of the number of CVD risk factors on discontinuation of b/tsDMARDs for different types of treatment failure in patients with RA. Previous reports have suggested that certain individual risk factors, such as obesity and smoking, can diminish the response to targeted therapies 10,14 . However, it remains uncertain whether this association is specific to primary or secondary treatment failure or an increased likelihood of experiencing side effects.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there have been no prior studies investigating the influence of the number of CVD risk factors on discontinuation of b/tsDMARDs for different types of treatment failure in patients with RA. Previous reports have suggested that certain individual risk factors, such as obesity and smoking, can diminish the response to targeted therapies 10,14 . However, it remains uncertain whether this association is specific to primary or secondary treatment failure or an increased likelihood of experiencing side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also ask "is rheumatoid sarcopenia a consequence of a more aggressive disease, and therefore, more difficult to treat…?" (1). We believe that the answer is quite likely yes.…”
Section: Carlosmentioning
confidence: 95%
“…With these comments, we hope that Dr. Dixit and other individuals who might have similar concerns can better understand the rationale for the strategies undertaken. (1), because rather than suggesting that obesity reduces the therapeutic response rate of patients with rheumatoid arthritis (RA) to both anti-tumor necrosis factor (TNF) and non-TNF therapies, the article adds that this problem is also related to underweight.…”
mentioning
confidence: 99%
“…Anti-TNF therapy reduces insulin resistance and improves insulin sensitivity in patients with severe RA. New findings have shown, however, that the efficacy of these agents in this regard is impaired by obesity [ 245 , 246 , 247 ].…”
Section: Dietary Factors On Mitochondrial Status In Ramentioning
confidence: 99%